English for Specific Purposes (ESP) (A Professional Needs Based Approach to English Language Learning) - Suri, Elda Martha; Saripa, Aisa Milan (The Future of Education Journal, 2026)
English for Specific Purposes (ESP) is an approach to English language teaching designed based on learners’ academic and professional needs. In the context of modern education, particularly in higher education and vocational education, the use of English for General Purposes (EGP) is considered insufficient to fully address the demands for specific language competencies aligned with particular fields of study and the workplace. Therefore, the implementation of ESP is essential to enhance the relevance of English language learning to learners’ real needs. This study aims to analyze the concept and characteristics of English for Specific Purposes and to examine its implementation in the learning process within educational settings. The research method employs a qualitative approach, with data collected through a literature review of books, national and international journal articles, and curriculum documents related to ESP instruction. The findings indicate that ESP learning based on needs analysis can improve learning motivation, contextual language understanding, and learners’ readiness to meet academic and professional demands. Moreover, ESP encourages educators to design contextual and relevant instructional materials. The implications of this study emphasize that integrating ESP into educational curricula is crucial for improving the quality of English language learning and producing graduates with language competencies aligned with their professional needs.